The subversion of the apocalypses in the Book of Jubilees - Hanneken, Todd Russell (Leiden Brill, 2012)
Jubilees uses the literary genre to raise the issues typical of apocalypses--including revelation, angels and demons, judgment, and eschatology--but rejects what the apocalypses typically say about those issues, subverting reader expectations with another view.
CSSP-7995 donated by Brill Publsihers through SPi Global Foundation, Inc.
Keywords: Book of Jubilees -- Criticism, Textual; Apocalyptic literature -- History and criticism; Hebrew language -- Morphology